Implementation of Spiral Modeling in the Design and Construction of the Paperless Office System for ITCC ITPLN Activity Documents - Mochamad Farid Rifai; Jatnika, Hendra; M. Yoga Distra Sudirman; Afifah Nurlita Octaviasari; Rizka Putri Aulia Rusdi; Fakhri Faros; M. Rafif Soniansyah (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2020)
The Information Technology Certification Center (ITCC) currently uses a manual system for creating financial accountability reports. This process is time-consuming and often leads to errors. Furthermore, because the necessary data is not centralized, data loss is a frequent problem, hindering the creation of accurate reports. To address these issues, the author developed "lpjkita," an application designed to streamline and improve the financial reporting process. The development employed the spiral model, which integrates risk management with iterative development and prototyping, while incorporating the structured approach of the waterfall model. This methodology allows for rapid development and gradual software improvement. The resulting application, "lpjkita," enables faster creation of financial accountability reports at ITCC, minimizes errors, and improves data recording. In addition to these benefits, the application also contributes to environmental sustainability by reducing paper consumption at ITCC, thereby mitigating the impact of global warming.